y''-2y'-3y=2e-x-10sinx
Let us solve the differential equation "y''-2y'-3y=2e^{-x}-10\\sin x." The characteristic equation "k^2-2k-3=0" is equivalent to "(k+1)(k-3)=0," and hence has the roots "k_1=-1,k_2=3."
The general solution of the differential equation is "y=C_1e^{-x}+C_2e^{3x}+y_p," where the particular solution is "y_p=axe^{-x}+b\\cos x+c\\sin x." Then "y'_p=ae^{-x}-axe^{-x}-b\\sin x+c\\cos x, y''_p=-ae^{-x}-ae^{-x}+axe^{-x}-b\\cos x-c\\sin x."
It follows that
"-2ae^{-x}+axe^{-x}-b\\cos x-c\\sin x-2(ae^{-x}-axe^{-x}-b\\sin x+c\\cos x)-3(axe^{-x}+b\\cos x+c\\sin x)=2e^{-x}-10\\sin x."
Then
"-4ae^{-x}+(-4b-2c)\\cos x+(2b-4c)\\sin x=2e^{-x}-10\\sin x."
We conclude that "-4a=2,-4b-2c=0, 2b-4c=-10." It follows that "a=-\\frac{1}{2},c=-2b, 10b=-10." Therefore, "a=-\\frac{1}{2}, b=-1,c=2."
We conclude that the general solutiion of the differential equation is
"y=C_1e^{-x}+C_2e^{3x}-\\frac{1}{2}xe^{-x}-\\cos x+2\\sin x."
Comments
Leave a comment